Managing Agricultural Biotechnology. Addressing Research Program Needs and Policy Implications - Cohen, Joel I. (International Service for National Agricultural Research, 1999)
As new technologies for improving agricultural production are constantly being developed, there is a great need to manage their implementation more effectively, to thereby enhance their impact. Over the past few years ISNAR, in collaboration with partners in developing countries, advanced research institutes, and international research centers, has been holding policy seminars and building a base of expertise for more effective management of agricultural biotechnology programs. This book covers the key managerial and policy issues that research directors, program managers, and policymakers face when building capacity and competency in biotechnology. The book includes syntheses and review chapters, as well as a number of country case studies - including Chile, Costa Rica, India, Indonesia, Japan, the Philippines, Singapore, and the United States. It consists of 24 chapters written by leading authorities in North and Latin America, Europe, Asia, and Australia. It is written in an accessible style that will appeal to practicing research managers as well as to academics in the disciplines of biotechnology, animal and plant breeding, and agricultural policy and development.